The impact of decreased expression of SVEP1 on abnormal neovascularization and poor prognosis in patients with intrahepatic cholangiocarcinoma - Chen, Liwei; He, Yuchao; Han, Zhiqiang; Gong, Wenchen; Tian, Xiangdong; Guo, Lin; Guo, Hua; Song, Tianqiang; Chen, Lu (Frontiers in Genetics, 2023)
Intrahepatic cholangiocarcinoma (ICC) is one of the most highly heterogeneous malignant solid tumors; it is generally insensitive to clinical treatment and has a poor prognosis. Evidence suggests that abnormal neovascularization in the tumor microenvironment is an important cause of treatment resistance as well as recurrence and metastasis, but the key regulatory molecules are still largely unknown and should be identified. We assessed the novel extracellular matrix protein (ECM) Sushi, von Willebrand factor type A, EGF and pentraxin containing 1 (SVEP1) expression pattern in the ICC by using immunohistochemistry. Multiplex immunofluorescence and Kaplan–Meier analysis were applied to explore the correlation between the low expression of SVEP1 and abnormal blood vessels and the clinical prognosis of ICC. Results showed that the expression of SVEP1 in most ICC samples was relatively lower than in the adjacent tissues. Statistical analysis suggested that patients with decreased SVEP1 expression always had shorter overall survival (OS) and disease-free survival (DFS). Moreover, the expression of SVEP1 was negatively correlated with the proportion of abnormal neovascularization in the tumor microenvironment of the ICC. Consistently, the key molecule of promoting vascular normalization, Ang-1, is positively correlated with the SVEP1 expression and prognosis in the ICC. In addition, the proportion of high Ki-67 expression was higher in the ICC samples with low SVEP1 expression, suggesting that the SVEP1 low expressed sample is in a malignant phenotype with high proliferation. This study reveals that SVEP1 is a promising prognostic biomarker for ICC and provides fresh insight into the role and potential new mechanism of abnormal neovascularization in ICC progression.